Jumps in option prices and their determinants: Real-time evidence from the E-mini S&P 500 option market - George Kapetanios; Michael Neumann; George Skiadopoulos (Queen Mary University of London, School of Economics and Finance, 2014)
We study the real-time characteristics and drivers of jumps in option prices. To this end, we employ high frequency data from the 24-hour E-mini S&P 500 options market. We find that option prices do not jump simultaneously across strikes and maturities and are uncorrelated with jumps in the underlying futures price. 14% to 28% of detected option price jumps occur around scheduled news releases. However, it is illiquidity rather than the news content that drives jumps. Evidence suggests that option traders increase bid-ask spreads to account for trading against investors who are skilled processors of public releases.
Keywords: C58; G10; G12; G13; 330; Asymmetric information; Co-jumps; Limit order markets; Liquidity; Option Markets; News announcements